ANALISIS HADIS TENTANG SHALAT TARWIH - Dame Siregar dan Desri Ari Enghariano (Institut Agama Islam Negeri Padangsidimpuan, 2020)
The tawih prayer arguments for the hadith ziyadah and shaz from al-Baihaqi. According to the argument, the name sohih is solat lail and in accordance with the Qur'an suroh al-Isro 'verse 79 and suroh al-Muzzammil verses 1-4 and verse 20 and other Sohih hadith. The implementation may be 4 + 4 + 3 prayer time or 2 + 2 + 2 + 2 + 2 + 1 prayer time 1 rakaat. Not true based on the history of an-Nasai number 1680 witr prayer 2 plus 1. It is better to be at home either in Romadon month or outside Romadon 11 rakaat. Do it according to the sohih argument.